The methodology of Abdullah Jahangir in analysing Christianity with special reference to pobitra Bible - Uddin, Md Helel (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, 2021)
The study of comparative religion did not begin until the 19th or 20th century. Many Muslim scholars studied comparative religions, used various methods, and developed religions other than Islam. The research has progressed over the phases of history, and its methodologies have also advanced along with modern sciences. Many Bangladeshi Muslim scholars have studied other religions, especially Christianity. They used several methods in response to Christian missionary propaganda against Islam and saved ordinary Muslims' faith. Christian missionary propaganda against Islam increased in the Indian subcontinent from the British colonies, including Bengal. After the independence of Bangladesh, missionary propaganda against Islam increased. They preached against other religions and converted poor people to Christianity in the name of various themes. It has been seen that in recent years, poor and uneducated people have been tempted to convert to Christianity by offering them multiple aids and that the number of converts to Christianity, especially Muslims, is increasing day by day. Many Bangladeshi ꜥulamā᾿ are currently using different methods, but the existing methods do not prevent people of other religions, including Muslims, from becoming Christians. However, it is an imperative and debatable issue to find such a methodology that helps prevent people, especially Muslims, from becoming Christians. This study aims to highlight and analyze the methods of an eminent Bangladeshi Muslim scholar, the late Khandaker Abdullah Jahangir, in the study of Christianity, emphasising his masterpiece Pobitra Bible Porichiti O Porjalochona, which is written in Bengali language. This study also attempts to explore the contributions of Abdullah Jahangir in the research of Christianity. Moreover, it highlights the socio-political conditions during Abdullah Jahangir's lifetime. The qualitative method is used for data collection and analysis in this study. This research has been conducted mainly based on library research, book, articles, online database, and textual analysis of Abdullah Jahangir works in the study of Christianity. This study found that Abdullah Jahangir used several methods in the study of Christianity, such as descriptive, textual, and logical approach that made him a prominent Muslim scholar in the study of Christianity in Bangladesh. This study also concludes that socio-political conditions greatly influence converting poor and uneducated people to Christianity in Bangladesh. Abdullah Jahangir's methodology can be followed to prevent people from becoming Christians, especially Muslims.